Exploring Students' Perceptions of Writing and Reading in the Digital Age - Femi Elegbeleye; Chuma Mbaleki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Digital transformation has significantly altered the ways students in higher education engage with reading and writing, shifting from traditional practices to the widespread use of digital tools. This study investigates first-year university students’ attitudes toward literacy in the digital age, with a particular focus on the influence of technology on their reading and writing behaviors. Drawing on quantitative data from the Beginning University Survey of Student Engagement (BUSSE), the research explores how students adapt to academic demands and how digital platforms such as Learning Management Systems (LMS) and AI-based applications affect their literacy practices. The findings reveal that students increasingly prefer digital resources, including e-books, online databases, and AI-assisted writing tools, which they perceive as enhancing efficiency, accessibility, and engagement. However, the study also identifies challenges such as increased digital distractions, reduced critical reading depth, and concerns about the reliability and originality of AI-generated content. The paper concludes that while digital tools can enrich literacy experiences, there is a critical need for universities to foster a balanced approach that combines digital and traditional literacy instruction. Such integration will help students develop comprehensive reading and writing competencies suited to the evolving academic landscape.